COMMUNICATIVE LANGUAGE TEACHING (CLT): A GOOD APPROACH FOR TEACHING ENGLISH - Hafiza Ilma Putri (UPT Perpustakaan Universitas Jambi, 2025)
One popular and successful approach to teaching English is Communicative Language Teaching (CLT). This method places a strong emphasis on the value of communication, practical language use, and cultural significance in language acquisition. This essay explores the theoretical foundations of CLT, how it is used, and the findings of numerous scholarly investigations. Expanded by academics such as Richards (2006) and Savignon (2018), CLT integrates linguistic, sociolinguistic, and pragmatic abilities to promote holistic language development. It is based on Hymes' (1972) notion of communicative competence. Through interactive, studentcentered activities including role-playing, group projects, and simulations, CLT improves students' fluency, accuracy, and self-confidence, according to research from Thailand (Jansem, 2019) and Indonesia (Istiantika et al., 2023). Despite the fact that CLT has numerous advantages, there are obstacles to its implementation, such a lack of resources, big class sizes, and different teacher skill levels (Richards, 2006; Butler, 2011; Istiantika et al., 2023). In order to create inclusive classroom environments and facilitate effective communicative tasks, teachers are essential (Littlewood, 2013; Jeon, 2009). This paper demonstrates how CLT prioritizes interaction and real-world language use in order to address the drawbacks of conventional language training approaches. However, sufficient teacher preparation, institutional support, and contextual adaptation are necessary for the effective application of CLT (Bax, 2003; Spada, 2007). This study highlights the transformative potential of CLT in altering English language education and preparing students for communication in a globalized environment by analyzing regional and global studies.